ERP Systems in the hospitality industry: value creation and critical success factors - Azevedo, P. S.; Azevedo, C.; Romão, M. (Egitania Sciencia, 2013)
The purpose of this paper is to highlight factors that may be considered critical to successful use of ERP (Enterprise Resource Planning) systems in the hospitality industry, in particular those that seem to be limiting a broader usage of these systems in this industry. The paper also contributes to the understanding of how ERP systems may create value to these industry´s businesses. This is done through a reference model, providing the framework to understand how the current vendor´s offer fits into the business needs of this industry. Os objetivos deste artigo são, por um lado, evidenciar os fatores considerados críticos para o sucesso da utilização dos sistemas do tipo ERP (Enterprise Resource Planning) na indústria hoteleira, evidenciando os que parecem estar a limitar o uso mais abrangente e integrado destes sistemas na indústria referida. Por outro lado, pretende-se com este artigo, através de um enquadramento referencial, perceber como os Sistemas ERP podem gerar mais valor para o negócio da indústria hoteleira, evidenciando como a oferta atual dos principais fornecedores de soluções tecnológicas se adequa às necessidades funcionais da indústria.